The association and potentially destructive role of Th9/IL‐9 is synergistic with Th17 cells by elevating MMP9 production in local lesions of oral lichen planus. (6th March 2018) - Wang, Hui; Guan, Xiaobing; Luo, Zhenhua; Liu, Yao; Ren, Qian; Zhao, Xin
Abstract : Background: This study was to investigate association and potentially destructive role of Th9/IL‐9 and their synergistic interaction with Th17 cells in elevating MMP9 production in local lesions of oral lichen planus (OLP) patients. Methods: Oral mucosal tissues were obtained from OLP patients and healthy controls (HC) and then divided into an epithelial part (EP) or a lamina propria part (LP). Both EP and LP subsets were assessed for IL‐9 and MMP9 mRNA levels by real‐time quantitative PCR (qPCR). Flow cytometry was used to detect the CD4+ T helper subset Th9 (IL‐9 + IL‐17 − CD4 + ) and Th17 (IL‐9 − IL‐17 + CD4 + ) in co‐cultured CD4+ Th cells and oral keratinocytes of OLP. IL‐9, IL‐17, and MMP9 in co‐culture supernatant were detected by ELISA. Results: The qPCR results demonstrated that IL‐9 and MMP9 mRNA levels were positively correlated in OLP lesions, and both significantly elevated in EP and LP lesions of erosive type OLP. Th9 and Th17 cells were significantly elevated in co‐cultures of CD4+ Th cells and keratinocytes, and MMP9, IL‐9, and IL‐17 levels were simultaneously increased. In vitro, recombinant human IL‐17 treatment significantly enhanced MMP9 protein and mRNA levels, while a synergistic effect of IL‐9 and IL‐17 was not observed. However, further results showed Th17 cells, IL‐17, and MMP9 were increased significantly when recombinant IL‐9 was added to the cultured CD4+ T cells. Conclusion: This study demonstrated that Th9/IL‐9 can induce elevated levels of MMP9 to aggravate OLP disease severity, which may occur directly through increasing Th17 levels or indirectly through a synergistic role with Th17.